Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physrevb.95.144408
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven Bose-Einstein condensation of magnons in antiferromagnets

Abstract: We explore routes to realize electrically driven Bose-Einstein condensation of magnons in insulating antiferromagnets. Even in insulating antiferromagnets, the localized spins can strongly couple to itinerant spins in adjacent metals via spin-transfer torque and spin pumping. We describe the formation of steady-state magnon condensates controlled by a spin accumulation polarized along the staggered field in an adjacent normal metal. Two types of magnons, which carry opposite magnetic moments, exist in antiferr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…As detailed in the supplemental material [59](see, also, references [61][62][63][64][65][66] therein), the interaction Hamiltonian [Eq. (3)] couples the NM electrons with the A and B sublattices of the AFMI: In order to obtain an effective interacting theory for electrons in NM, we integrate out the magnons, using a canonical transformation [60].…”
Section: Afmi Nmmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in the supplemental material [59](see, also, references [61][62][63][64][65][66] therein), the interaction Hamiltonian [Eq. (3)] couples the NM electrons with the A and B sublattices of the AFMI: In order to obtain an effective interacting theory for electrons in NM, we integrate out the magnons, using a canonical transformation [60].…”
Section: Afmi Nmmentioning
confidence: 99%
“…From the interaction Hamiltonian we obtain, for coupling to sublattice A and B respectively [20,61],…”
Section: Modelmentioning
confidence: 99%
“…In addition, it was shown that thermal magnon transport takes place at zero spin bias when the sublattice symmetry is broken at the interfaces, e.g., induced by interfacial magnetically uncompensated AF order [20]. Complementarily, coherent spin transport induced by spin accumulation has been earlier considered and predicted to result in spin superfluidity [21,22] or Bose-Einstein condensates of magnons [23]. Recently, it has been shown via non-local spin transport measurements that magnons remarkably propagate at long distances in insulating AFs; α-Fe 2 O 3 [24], Cr 2 O 3 [25] and MnPS 3 [26].…”
Section: Introductionmentioning
confidence: 99%
“…We disregard terms of second order in the magnon operators from H Int . Then, the total Hamiltonian H = H L AFI + H R AFI + H NM + H Int is given by [5]…”
Section: Modelmentioning
confidence: 99%
“…Even so, AFIs have received less attention than ferromagnetic insulators (FIs) in spintronics. A standard model for the interfacial tie is an exchange coupling between the itinerant electrons and the localized spins [4][5][6]. In this formalism, the electrons experience a staggered field and scatter through two different scattering channels: a regular channel and an Umklapp channel [4,5].…”
Section: Introductionmentioning
confidence: 99%